Research on densification mechanism of Inconel 718 alloy miniature gear by electric field-assisted sintering. Issue 1 (1st December 2022) - Ma, L Y; Meng, B; Zhang, Z Y; Wan, M
Abstract : The densification mechanism of the electric field-assisted sintering (E-FAST) for Inconel 718 alloy miniature gears was studied using the Bernard-Granger model. Under the conditions of sintering temperature of 950 °C, 1000 °C and 1050 °C and dwelling time of 240 s, 300 s and 360 s, the Inconel 718 powders were subjected to E-FAST using the Gleeble thermal simulator, and the densification rate was up to 10 −3 s −1 . With the increase of the sintering temperature, the peak of the densification rate of the sintered sample was enlarged, and the time for the peak to appear became shorter. The densification of Inconel 718 alloy miniature gears was mainly concentrated in the dwelling stage. When the dwelling time reached 300 s, the densification rates of the samples under different temperature conditions were similar, indicating that the gear samples were close to full density at this time. Simulation and sintering test results show that the densification stages of the gear samples can be divided into low sintering stress stage with stress index n = 0.4 and high sintering stress stage with stress index n = 3.5. The apparent activation energy of the densification changes with the variation of the sintering stress stage.